Hubungan Fasilitas Bengkel terhadap Hasil Belajar Teknik Pemesinan Bubut - Saputra, Muhammad Pandi; Syahri, Budi; Irzal, Irzal; Abadi, Zainal (Al-DYAS, 2024)
This research focuses on investigating the relationship between workshop facilities and the learning outcomes of lathe machining techniques. The instruments used in this study include questionnaires, practical performance scores, and documentation. A quantitative research method with a descriptive correlational approach was employed. The study took place at SMK Negeri 1 Lintau Buo, with the research subjects being 11th-grade Mechanical Engineering students. The research was conducted in November, and the sample size was determined to be 54 students, divided into two classes: 28 students in class XI Mechanical Engineering 1 and 26 students in class XI Mechanical Engineering 2. The data analysis results indicate a significant and positive correlation between theoretical knowledge and practical outcomes, with a correlation coefficient of 0.625 and a significance value (2-tailed) of 0.000. Therefore, it can be concluded that there is a positive and significant relationship between workshop facilities and the learning outcomes of lathe machining techniques for 11th-grade students at SMK Negeri 1 Lintau Buo. This implies that the relationship between workshop facilities and the learning outcomes of lathe machining techniques falls into the strong category.